Přehledové studie: jejich typologie, funkce a způsob vytváření. / Reviews: Their typology, functions and how to write them. - Jiří Mareš (Czech Pedagogical Society, 2013)
The study informs the reader about how to write a quality review, which would summarize the current knowledge of the selected researchtopic. The aim of this study is to present a typology of review studies, to characterize various functions performed by different types of review studies; to show how to proceed in the selection of topics, at the preparation of supporting documents, and at the actual writing a review. The first part presents 11 types of review studies, both the generally known and the less known ones. The second part is a brief overview of the genres that do not belong to the category of review studies. The third part characterizesdifferent functions that are fulfilled by the reviews (the reviewstudies may facilitate understanding of the presented research, they are beneficial to the study's author, to the development of the field or to other researchers). The fourth section of the text looks closer at the problems faced by the author when choosing the topic for thereview study, and offers possible solutions. The fifth part summarizes the procedures for preparation of documents for a review study (literature research, reduction of the initial selected works, critical reading, text analysis, creation of review tables). Thesixth section provides advice on how to proceed in the actual writing a review. Where appropriate, in addition to recommendations on how to proceed, typical mistakes are mentioned that should be avoided by the author. In developed countries, there are three types of materials teaching students and young scientists how to write a reviewstudy. These guidelines can be found on the University website (usually within so called Writing Centres) or are available as journal articles on this topic or there are more comprehensive guides. So far, there has not been such a set of guidelinesavailable in the Czech Republic. The present overview tries to fill this gap. Apart from general advice and guidelines, it is completed with some practical examples.